Association of Testosterone Replacement Therapy and the Incidence of a Composite of Postoperative In-hospital Mortality and Cardiovascular Events in Men Undergoing Noncardiac Surgery. (September 2017) - Argalious, Maged Y.; You, Jing; Mao, Guangmei; Ramos, Daniel; Khanna, Sandeep; Maheshwari, Kamal; Trombetta, Carlos
Abstract : Background: Whether patients on testosterone replacement therapy undergoing noncardiac surgery have an increased risk of postoperative in-hospital mortality and cardiovascular events remains unknown. We therefore sought to identify the impact of testosterone replacement on the incidence of a composite of postoperative in-hospital mortality and cardiovascular events in men undergoing noncardiac surgery. Methods: Data from male American Society of Anesthesiologists I through IV patients 40 yr or older who underwent noncardiac surgery between May 2005 and December 2015 at the Cleveland Clinic (Cleveland, Ohio) main campus were included. The primary exposure was preoperative testosterone use. The primary outcome was a composite of postoperative in-hospital mortality and cardiovascular events. We compared patients who received testosterone and those who did not using propensity score matching within surgical procedure matches. Results: Among 49, 273 patients who met inclusion and exclusion criteria, 947 patients on testosterone were matched to 4, 598 nontestosterone patients. The incidence of in-hospital mortality was 1.3% in the testosterone group and 1.1% in the nontestosterone group, giving an odds ratio of 1.17 (99% CI, 0.51 to 2.68; P = 0.63). The incidence of myocardial infarction was 0.2% in the testosterone group and 0.6% in the nontestosterone group (odds ratio = 0.34; 99% CI, 0.05 to 2.28; P = 0.15). Similarly, no significant difference was found in stroke (testosterone vs. nontestosterone: 2.0% vs . 2.1%), pulmonary embolism (0.5% vs . 0.7%), or deep venous thrombosis (2.0% vs . 1.7%). Conclusions: Preoperative testosterone is not associated with an increased incidence of a composite of postoperative in-hospital mortality and cardiovascular events. Abstract : In a single-center observational analysis, testosterone replacement therapy was not associated with a measurable increase or decrease in cardiovascular events or mortality within 30 days of surgery.